2005
DOI: 10.1351/pac200577020429
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional transition map of flattening behavior in the thermal spray process

Abstract: Many kinds of both metallic and ceramic powder particles were plasma-sprayed onto the mirror-polished metallic substrate surface, and the effect of both substrate temperature and ambient pressure on the flattening behavior of the particle was systematically investigated. In the flattening behavior of the sprayed particle onto the substrate surface, critical conditions were recognized both in the substrate temperature and ambient pressure. That is, the flattening behavior changed transitionally on that critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 1 publication
2
44
0
Order By: Relevance
“…By introducing the measured temperature into each physical constant (i.e., density, surface tension, and viscosity), the actual K value was calculated for several kinds of sprayed metallic materials. As a result, it was found that K values in each sprayed particle were remarkably larger compared to Kc, regardless of the sprayed material [3]. It means that the regular thermally sprayed particles have enough higher driving force for the splashing.…”
Section: Transition Mechanism In Metallic Materialsmentioning
confidence: 93%
See 1 more Smart Citation
“…By introducing the measured temperature into each physical constant (i.e., density, surface tension, and viscosity), the actual K value was calculated for several kinds of sprayed metallic materials. As a result, it was found that K values in each sprayed particle were remarkably larger compared to Kc, regardless of the sprayed material [3]. It means that the regular thermally sprayed particles have enough higher driving force for the splashing.…”
Section: Transition Mechanism In Metallic Materialsmentioning
confidence: 93%
“…Correspondingly, it was confirmed that the coating adhesive property on the blasted substrate surface changes transitionally on those critical temperature and pressure ranges, respectively. Based on the results, three-dimensional transition curvatures by combining both transition curves was proposed for each sprayed material, as a controlling principle for the practical usage in the thermal spray industries [3]. Namely, information given in the single splat has a meaningful contribution onto the practical usage of the thermal spraying.…”
Section: Introductionmentioning
confidence: 99%
“…From the unsymmetrical width of the extending sheet in the horizontal direction, it can be conjectured that the thin film is lifted from the substrate surface and expanding into the air. This is most likely due to the fact that the substrate was not preheated and the wetting by the molten droplet was poor (5) . Even though efforts to capture the spreading/cooling phenomenon on a preheated substrate were done, it was not successful due to the too short spreading time limited by rapid solidification by the improved contact with the substrate.…”
Section: Observation Of Single Splat Formationmentioning
confidence: 99%
“…[1][2][3][4][5] This technique provides thick coating layers over a large surface at a high deposition rate and improves surface properties of substrates such as appearance, adhesion, wettability, wear resistance, and thermal resistance. While many factors affecting coating quality and corresponding reliability have been reported in the literature, [6][7][8][9] detailed technologies and fundamentals to control those factors are not comprehensively understood yet. In the thermal spray coating process, adhesive and cohesive quality between molten droplets and target substrates can be sufficiently controlled by three representative factors as follows; thermal properties, impact dynamics and operating conditions, and surface characteristics.…”
Section: Introductionmentioning
confidence: 99%